Effects and Moderators of Computer-Based Training on Children's Executive Functions: A Systematic Review and Meta-Analysis - Cao, Yifei; Huang, Ting; Huang, Jipeng; Xie, Xiaochun; Wang, Yuan (Frontiers in Psychology, 2020)
Computer-based training has attracted increasing attention from researchers in recent years. Several studies have found that computer-based training resulted in improved executive functions (EFs) in adults. However, it remains controversial whether children can benefit from computer-based training and what moderator could influence the training effects. The focus of the present meta-analysis was to examine the effects of computer-based training on EFs in children: working memory, cognitive flexibility, and inhibitory control. A thorough search of published work yielded a sample of 36 studies with 216 effect sizes. The results indicated that computer-based training showed moderate training effects on improving EFs in children (g = 0.35, k = 36, p < .001), while training effects of working memory were significantly higher. Furthermore, we found near-transfer effects were marginally significantly higher than far-transfer effects. The standard training method was significantly more effective than training with game elements. In computer-based training, typically developing children had significantly better training effects than atypically developing children. In addition, factors like the number of training sessions and age modulated the training effects. The present study is the first meta-analysis to investigate the effects and moderators of computer-based training for children’s EFs. The results provided evidence that computer-based training (especially standard training) may serve as an efficient way to improve EFs in children (especially typically developing individuals). We also discussed some directions for future computer-based training studies